The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.imlet.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Will a little change do you good? A putative role of polymorphisms in COVID-19

Abstract: An alarming disease caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) named COVID-19 has emerged as an unprecedented public health problem and ignited a world health crisis. As opposed to what was believed at the beginning of the pandemic, the virus has not only spread but persevere causing secondary waves and challenging the concept of herd immunity against viral infections. While the majority of SARS-CoV-2-infected individuals may remain asymptomatic, a fraction of individuals ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Therefore, although promising, these two mediators should be considered carefully as targets for COVID-19 therapy with anti-IL-6 and anti-TNF monoclonal antibodies. Regarding the Interferon pathway, specific polymorphisms in genes related to cytokines are strongly associated with disease outcome, such as Interferon related genes (34,35). Recent investigations have shown that a worst COVID-19 outcome is closely associated to polymorphisms in genes related to the production of proinflammatory IFN-g and IL-12 (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although promising, these two mediators should be considered carefully as targets for COVID-19 therapy with anti-IL-6 and anti-TNF monoclonal antibodies. Regarding the Interferon pathway, specific polymorphisms in genes related to cytokines are strongly associated with disease outcome, such as Interferon related genes (34,35). Recent investigations have shown that a worst COVID-19 outcome is closely associated to polymorphisms in genes related to the production of proinflammatory IFN-g and IL-12 (25).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our results show lower levels of IFN-g in the airway of critically ill COVID-19 patients that progress to death, which suggests the protective role of this cytokine against SARS-CoV-2 infection. In addition, high expression of IFNAR2 interferon receptor subunit reduced the chances of severe COVID-19, indicating that the proinflammatory profile of cytokines are important to disease outcome in COVID-19 (34,35). In fact, lower levels of circulating IFN-g were associated to a higher risk of lung fibrosis in COVID-19 patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…IL1 RN (rs315952—T/C) and IL4 (rs2070874—C/T/ IL4 + 1059 C/T) SNPs have been associated with COVID‐19 severity. 55 , 56 The SNPs in the IL6 gene have been associated with pneumonia and COPD and also certain viral infections such as hepatitis B virus, hepatitis C virus (HCV), and influenza virus. 57 , 58 , 59 Low rate of IL6 CC (rs1800795) SNP was related to the persistence of HCV infection.…”
Section: Interleukins Polymorphismsmentioning
confidence: 99%
“…The different expression of cytokines caused by point mutations in these genes interferes in the evolution of the immune response and in the different clinical outcomes of COVID-19. These polymorphisms can also affect the response to the use of therapies and vaccines [164].…”
Section: Cytokine Polymorphismmentioning
confidence: 99%